Thyroid‐stimulating hormone is an independent risk factor of non‐alcoholic fatty liver disease. Issue 3 (1st October 2019) - Tahara, Kazuki; Akahane, Takemi; Namisaki, Tadashi; Moriya, Kei; Kawaratani, Hideto; Kaji, Kosuke; Takaya, Hiroaki; Sawada, Yasuhiko; Shimozato, Naotaka; Sato, Shinya; Saikawa, Soichiro; Nakanishi, Keisuke; et al.
Abstract : Background and Aim: Hypothyroidism might play a crucial role in the pathogenesis of non‐alcoholic fatty liver disease (NAFLD). The association of subclinical hypothyroidism with NAFLD has been inconsistent. The relationship of NAFLD with thyroid function parameters and subclinical hypothyroidism was determined. Methods: This cross‐sectional study included 70 patients with subclinical hypothyroidism and 70 controls with euthyroidism matched according to gender, age, and body mass index (BMI). NAFLD was diagnosed via abdominal ultrasonography. The association between NAFLD and subclinical hypothyroidism was analyzed. Results: The prevalence of NAFLD was significantly higher in patients with subclinical hypothyroidism than in those with euthyroidism. Multivariate analysis showed that subclinical hypothyroidism was an independent risk factor of NAFLD adjusted by metabolic‐related factors, such as BMI, triglyceride, high‐density lipoprotein‐cholesterol, hypertension, and diabetes. Thyroid‐stimulating hormone (TSH) was an independent risk factor of NAFLD adjusted by the same metabolic‐related factors, but free thyroxine (FT4) was not a risk factor. The FIB‐4 index, a noninvasive marker of liver fibrosis was significantly higher in patients with subclinical hypothyroidism than in those with euthyroidism. Compared with patients with euthyroidism, the proportion of the FIB‐4 index ≥2.67 was significantly higher, and the proportion of the FIB‐4 index <1.30 was lower in patients with subclinical hypothyroidism. Conclusions: TSH elevation even within the euthyroid range is an independent risk factor of NAFLD and may influence the progression of liver fibrosis, even with a normal FT4 level. Abstract : Thyroid‐stimulating hormone elevation, even within the euthyroid range, is an independent risk factor of non‐alcoholic fatty liver disease and may have an influence on the progression of liver fibrosis, even with a normal free T4 level.